A floral‐derived attractant for Aedes aegypti mosquitoes. Issue 3 (17th April 2015) - von Oppen, S.; Masuh, H.; Licastro, S.; Zerba, E.; Gonzalez‐Audino, P.
Abstract The reproductive success of Aedes aegypti (L.) (Diptera: Culicidae) is strongly dependent on the availability of carbohydrates in the environment and the ability of the mosquitoes to locate them. The most significant source of carbohydrates for mosquitoes is nectar from flowering plants, which mosquitoes locate by their volatile compounds. The aim of our work was to identify plant volatile compounds that elicit a behavioral response in Ae. aegypti, which may be included in a mosquito trap for surveillance and/or control purposes. Landing‐preference bioassays were performed with plants of three species—Plectranthus neochilus Schltr. (Lamiaceae), Tagetes patula L. (Asteraceae), and Lobularia maritima (L.) Desv. (Brassicaceae)—as lures and toxic sugar baits as landing markers. Mosquitoes landed only on L. maritima. Freshly cut inflorescences of L. maritima elicited a positive flight response in both sexes of mosquitoes. The analysis of the compounds in the static head space of L. maritima was performed by solid phase microextraction (SPME). Of the single volatile compounds tested, acetophenone was attractive and 1‐octanol caused a flight aversive response. These findings are relevant as there are no reported plant‐derived compounds attractive to A. aegypti. As both the male and female mosquitoes sugar feed, traps baited with plant odors are able to lure the whole adult population, making it an interesting option for including in future mosquito surveillance traps.